2014
DOI: 10.1186/1556-276x-9-346
|View full text |Cite
|
Sign up to set email alerts
|

Size evolution of ion beam synthesized Pb nanoparticles in Al

Abstract: The size evolution of Pb nanoparticles (NPs) synthesized by ion implantation in an epitaxial Al film has been experimentally investigated. The average radius R of Pb NPs was determined as a function of implantation fluence f. The R(f) data were analyzed using various growth models. Our observations suggest that the size evolution of Pb NPs is controlled by the diffusion-limited growth kinetics (R2∝f). With increasing implantation current density, the diffusion coefficient of Pb atoms in Al is evident to be enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Rutile compared to other phases has more stability while anatase and brookite are metastable and can be easily transformed to anatase by heating [19,20]. Annealing at 600 o C creates rutile phase in annealed TiO2 [21]. Some recent studies reported the effect of heat treatment and annealing time and temperature on structural, mechanical, and optical properties of TiO2 thin films [22][23][24][25].…”
mentioning
confidence: 99%
“…Rutile compared to other phases has more stability while anatase and brookite are metastable and can be easily transformed to anatase by heating [19,20]. Annealing at 600 o C creates rutile phase in annealed TiO2 [21]. Some recent studies reported the effect of heat treatment and annealing time and temperature on structural, mechanical, and optical properties of TiO2 thin films [22][23][24][25].…”
mentioning
confidence: 99%
“…The obtained bandgap narrowing in anatase due to the V impurity has been also observed in small supercell (24 atoms) computations. 25 The fact of bandgap shrinking provides a major avail in use of the V-doped anatase as an active photocatalyst.…”
Section: Impurity Doping In Anatase Crystalmentioning
confidence: 99%
“…[10][11][12][13] A binder-free electrode provides an effective mass and charge exchange by preventing the formation of "dead surface". 14,15 Current study reports preparation and electrochemical analysis of new copper-doped manganese nanoferrite (Cu x Mn (1-x) Fe 2 O 4 ) for use as low-cost electrode material for various energy devices. A hybrid of the nanoferrites with polyaniline (PANI) can be used as electrode materials for fabricating a high-performance symmetrical supercapacitor without any use of binders.…”
mentioning
confidence: 99%